Association of frailty status with overall survival in elderly hypertensive patients: based on the Chinese Longitudinal Healthy Longevity Survey - Liying Li; Yueting Liang; Dajun Xin; Lu Liu; Zhuomin Tan; Ziqiong Wang; Muxin Zhang; Haiyan Ruan; Liming Zhao; Kexin Wang; Yi Zheng; Ningying Song; et al. (BMC, 2024)
Abstract Background Hypertension and frailty often coexist in older people. The present study aimed to evaluate the association of frailty status with overall survival in elderly hypertensive patients, using data from the Chinese Longitudinal Healthy Longevity Survey. Methods A total of 10,493 elderly hypertensive patients were included in the present study (median age 87.0 years, 58.3% male). Frailty status was assessed according to a 36-item frailty index (FI), which divides elderly individuals into four groups: robustness (FI ≤ 0.10), pre-frailty (0.10 < FI ≤ 0.20), mild-frailty (0.20 < FI ≤ 0.30), and moderate-severe frailty (FI > 0.30). The study outcome was overall survival time. Accelerated failure time model was used to evaluate the association of frailty status with overall survival. Results During a period of 44,616.6 person-years of follow-up, 7327 (69.8%) participants died. The overall survival time was decreased with the deterioration of frailty status. With the robust group as reference, adjusted time ratios (TRs) were 0.84 (95% confidence interval [CI]: 0.80-0.87) for the pre-frailty group, 0.68 (95% CI: 0.64-0.72) for the mild frailty group, and 0.52 (95% CI: 0.48-0.56) for the moderate-severe frailty group, respectively. In addition, restricted cubic spline analysis revealed a nearly linear relationship between FI and overall survival (p for non-linearity = 0.041), which indicated the overall survival time decreased by 17% with per standard deviation increase in FI (TR = 0.83, 95% CI: 0.82-0.85). Stratified and sensitivity analyses suggested the robustness of the results. Conclusions The overall survival time of elderly hypertensive patients decreased with the deterioration of frailty status. Given that frailty is a dynamic and even reversible process, early identification of frailty and active intervention may improve the prognosis of elderly hypertensive patients.